A Comparative Study of Short Linear Motif Compositions of the Influenza A Virus Ribonucleoproteins - Yang, Chu-Wen (PLOS ONE, 2012)
Protein-protein interactions through short linear motifs (SLiMs) are an emerging concept that is different from interactions between globular domains. The SLiMs encode a functional interaction interface in a short (three to ten residues) poorly conserved sequence. This characteristic makes them much more likely to arise/disappear spontaneously via mutations, and they may be more evolutionarily labile than globular domains. The diversity of SLiM composition may provide functional diversity for a viral protein from different viral strains. This study is designed to determine the different SLiM compositions of ribonucleoproteins (RNPs) from influenza A viruses (IAVs) from different hosts and with different levels of virulence. The 96 consensus sequences (regular expressions) of SLiMs from the ELM server were used to conduct a comprehensive analysis of the 52,513 IAV RNP sequences. The SLiM compositions of RNPs from IAVs from different hosts and with different levels of virulence were compared. The SLiM compositions of 845 RNPs from highly virulent/pandemic IAVs were also analyzed. In total, 292 highly conserved SLiMs were found in RNPs regardless of the IAV host range. These SLiMs may be basic motifs that are essential for the normal functions of RNPs. Moreover, several SLiMs that are rare in seasonal IAV RNPs but are present in RNPs from highly virulent/pandemic IAVs were identified. The SLiMs identified in this study provide a useful resource for experimental virologists to study the interactions between IAV RNPs and host intracellular proteins. Moreover, the SLiM compositions of IAV RNPs also provide insights into signal transduction pathways and protein interaction networks with which IAV RNPs might be involved. Information about SLiMs might be useful for the development of anti-IAV drugs.